Fluctuation of zonulin levels in blood vs stability of antibodies - Vojdani, Aristo; Vojdani, Elroy; Kharrazian, Datis (World journal of gastroenterology : WJG, 2017)
AIM To evaluate the measurement of zonulin level and antibodies of zonulin and other tight junction proteins in the blood of controls and celiac disease patients.METHODS This study was conducted to assess the variability or stability of zonulin levels vs Ig A and Ig G antibodies against zonulin in blood samples from 18 controls at 0, 6, 24 and 30 h after blood draw. We also measured zonulin level as well as zonulin, occludin, vinculin, aquaporin 4 and glial fibrillary acidic protein antibodies in the sera of 30 patients with celiac disease and 30 controls using enzyme-linked immunosorbent assay methodology. RESULTS The serum zonulin level in 6 out of 18 subjects was low or < 2.8 ng/m L and was very close to the detection limit of the assay. The other 12 subjects had zonulin levels of > 2.8 ng/m L and showed significant fluctuation from sample to sample. Comparatively, zonulin antibody measured in all samples was highly stable and reproducible from sample to sample. Celiac disease patients showed zonulin levels with a mean of 8.5 ng/m L compared to 3.7 ng/m L in controls(P < 0.0001). Elevation of zonulin level at 2SD above the mean was demonstrated in 37% of celiac disease patients, while antibodies against zonulin, occludin and other tight junction proteins was detected in up to 86% of patients with celiac disease. CONCLUSION Due to its fluctuation, a single measurement of zonulin level is not recommended for assessment of intestinal barrier integrity. Measurement of Ig G and Ig A antibodies against zonulin, occludin, and other tight junction proteins is proposed for the evaluation of the loss of intestinal barrier integrity.